ANALISIS PENINGKATAN AIR PAM KAPASITAS 60 LITER/DETIK DI DESA TEGUR WANGI PAGAR ALAM SUMATERA SELATAN - Hendra Hendra; Diana Suita Harahap (Universitas Islam Sumatera Utara, 2021)
Water is a very important necessity for the lives of all living things. Along with the development of civilization and population growth, pollution and impurity of water also increased. In fact, the quality of the water is very important because it relates to human health. Therefore, proper water treatment is needed so that the quality of drinking water and clean water can be full filled. The main purpose of writing this report is to find out how the pump water treatment process in PDAM Pagar Alam City. From the observations ie : (1). Debit meter using Thomson measuring instrument is simpler and bias used for discharge 100 l/dt. (2). Channel to Flokulator with length 2 meters, height 1 meter and width 1 meter. (3). Sedimentation with inlet channel size measuring 1 meter wide, water height 3.98 meters and length 6.0 meters. (4). Deposition zone with length 4.6 meters, width 6 meters, plate height 0.87 meters and number of flate 51 pieces. (5). Outlet zone used with outlet diameter of 0.3 meters. (6). Mud zone with a drain diameter of 0.5 meters. (7).Filter with gutter number 1 piece, length 3 meters, width 0.3 meter, 0,3 meters and with a drain pipe diameter of 300 meters. (8).Container with a length of 12 meters, width 3 meters, height 4 meters, pipe diameter to reservoir 200 meters with a stay time of 30 minutes. (9). Disinfection with m³ body volume, length 0.5 meters, width 0.5 meters and height 0.5 meters. The water treatment process in PDAM Pagar Alam City follows the standard stipulated in PERMENKES RI No. 492/MENKES/PER/IV/2010.